Peculiarities of training future food industry engineers for creative vocational activities - Kurilo, Olga (ScienceRise: Pedagogical Education, 2020)
The article theoretically substantiates the peculiarities of preparation of future engineers-educators of the food industry for the creative vocational activity and defines ways of this preparation. Modern requirements for engineers-educators of the food industry in the field of industry and education are the formation of the readiness for the creative vocational activity, which includes the ability of these specialists to meet the growing needs of the consumer and production; the appropriate level of knowledge in the disciplines of vocational and practical training, possessing vocational and practical skills, which in turn will become a good basis for the vocational solution of specific production situations that occur daily in enterprises of the food industry and educational process. The potential opportunities of educational programs of the specialty 015 Vocational Education (Food technology) for ensuring the formation of the readiness of future engineers-educators of the food industry of the educational degree of a bachelor to the creative vocational activity are identified. The ways of improving the preparation of future engineers-educators for the creative vocational activity are determined. In particular, the orientation of training on the optimal realization of the creative potential of future specialists and the creation of appropriate organizational and pedagogical conditions (activation of higher education candidates’ motives for creative expression in future vocational activities, use of the didactic opportunities of the disciplines of the cycle of vocational and practical training in achieving the expected creative results; organization of psychological and pedagogical support with seekers of higher education on the formation of components of readiness the for the creative vocational activity). The offered research allows to decide the problems of the staff of labour migration at the level of providing the high-quality trade education and learning, in particular in the context of strengthening the skilled potential of the food industry on their readiness to be quickly oriented in the changing terms of labour in the field of industry and education